Effect of the physicochemical changes in the antimicrobial durability of green synthesized silver nanoparticles during their long-term storage. Issue 47 (25th October 2022) - Habibullah, Giyaullah; Viktorova, Jitka; Ulbrich, Pavel; Ruml, Tomas
Abstract : A new method for light induced green synthesis of silver nanoparticles that supports long-term stability. Elevation of oxidation and dissolution levels with time directly impacts the long-term stability and antimicrobial durability. Abstract : It is generally recognized that the stability of nanoparticles (NPs) has a great impact on their potential biological applications. Despite this, very few studies have investigated the change in toxicity of NPs over time but none has studied the periodic physicochemical changes contributing to it. To address this, we analyzed the effects of long-term storage on the physicochemical changes of green synthesized silver nanoparticles (AgNPs) that directly influences their antimicrobial durability. Light-induced slow synthesis of AgNPs was carried out using Saraca asoca aqueous leaf extract. The synthesis was optimized with respect to parameters known to play a major role in the long-term stability of AgNPs: pH, temperature, light exposure time, AgNO3 concentration, extract proportion in the reaction mixture and storage conditions. Freshly synthesized AgNPs were characterized and then stored under optimized conditions. UV-vis spectrophotometry, AAS, conventional TEM and HR-TEM along with EDX spectroscopy were used at regular intervals to test the physicochemical properties that influence their long-term stability. Broth dilution assay was used to test antimicrobial activity of AgNPs against Escherichia coli and Staphylococcus aureus . Under dark storage conditions at room temperature, the AgNPs exhibited excellent stability with very good dispersity, throughout the study period of 18 months, despite the particles undergoing physicochemical changes in largescale. AgNPs exhibited sufficient antimicrobial activity against both strains tested. Due to the stronger stabilizing effect of the extract, we observed the lowest inhibition of E. coli and S. aureus by the freshly synthesized and 15 day old AgNPs; however, the inhibition rate escalated after a month and the highest rate of inhibition was observed with the particles between 2 months to 6 months of storage. After 6 months, we observed the particles losing their antimicrobial potential gradually, that lasted throughout the rest of our study period. This observation was in accord with the physicochemical changes that AgNPs were undergoing with time. By deepening our understanding of the changes in the physicochemical properties of green synthesized AgNPs over time, this study contributes to the development of more effective, durable, and potent AgNPs.